Vergadering in Utrecht. Geheel rechts: Van der Louw, naast hem: Vondeling, applaudiserend: De Jong - Koch, Eric
Vergadering in Utrecht. Geheel rechts: Van der Louw, naast hem: Vondeling, applaudiserend: De Jong.